Hubungan Antara Kecerdasan Moral dengan Kecerdasan Sosial Siswa SD Kelas IV Gugus XII Kota Bengkulu - Suherli, Nada; Lusa, Herman; Agusdianita, Neza (Jurnal PGSD, 2019)
This study aims to determine the relationship between moral intelligence and social intelligence of elementary school students Class IV XII Bengkulu City. This type of research is quantitative research using correlational research method. The population in this study all elementary school students Gugus XII Bengkulu City as much as 4 elementary school with 240 students. The sample in this study were 34 students taken proportionately. Data collection techniques and instruments in this study using a questionnaire. Data analysis technique using product moment correlation formula and t test. The results of this study indicate that the value of r hitung = 0.471 is greater than r tabel = 0.339, with contribution percent 22.17% and at significant level (t hitung) 3.019 which means Ha accepted. Thus it can be concluded that there is a relationship between moral intelligence and social intelligence of elementary school students in grade IV XII of Bengkulu City.